Complex Interactions of Temperature, Light and Tissue Damage on Seagrass Wasting Disease in Zostera marina - Jakobsson-Thor, Stina; Brakel, Janina; Toth, Gunilla B.; Pavia, Henrik (Frontiers in Marine Science, 2020)
The temperate seagrass species eelgrass Zostera marina can be infected by the wasting disease pathogen Labyrinthula zosterae, which is believed to have killed about 90% of the seagrass in the Atlantic Ocean in the 1930s. It is not known why this opportunistic pathogen sometimes becomes virulent, but the recurrent outbreaks may be due to a weakening of the Z. marina plants from adverse environmental changes. This study investigated the individual and interactive effects of multiple extrinsic factors (temperature, light, and tissue damage) on the host-pathogen interaction between Z. marina and L. zosterae in a fully crossed infection experiment. The degree of infection was measured as both lesion coverage and L. zosterae cell concentration. We also investigated if the treatment factors affect the chemical defense of the host, measured as the inhibitory capacity of seagrass extracts in bioassays with L. zosterae. Finally, gene expression of a set of targeted genes was quantified in order to investigate how the treatments change Z. marina’s response to infection. Light had a pronounced effect on L. zosterae infection measured as lesion coverage, where reduced light conditions increased lesions by 35%. The response to light on L. zosterae cell concentration was more complex and showed significant interaction with the temperature treatment. Cell concentration was also significantly affected by physical damage, where damage surprisingly resulted in a reduced cell concentration of the pathogen. No treatment factor caused detectable decrease in the inhibitory capacity of the seagrass extracts. There were several interactive effects between L. zosterae infection and the treatment factors on Z. marina growth, and on the expression of genes associated with immune defense, phenol synthesis and primary metabolism, showing that the molecular reaction towards L. zosterae infection depends on prevailing environmental conditions. Our study shows that individual or interactive effects of light, temperature and tissue damage can affect multiple aspects of host-pathogen interactions in seagrass. These results highlights the complexity of marine host-pathogen systems, showing that more multi-factorial investigations are needed to gain a better understanding of disease in marine plants under different environmental conditions.